Incidence and severity of G6PI-induced arthritis are not increased in genetically distinct mouse strains upon aging. - Andreas, Nico; Muller, Sylvia; Templin, Nicole; Jordan, Paul M.; Schuhwerk, Harald; Mueller, Michael; Gerstmeier, Jana; Miek, Laura; Andreas, Saskia; Werz, Oliver; Kamradt, Thomas (Arthritis Research & Therapy, 2021)
BACKGROUND: The incidence of rheumatoid arthritis is correlated with age. In this study, we analyzed the association of the incidence and severity of glucose-6-phosphate isomerase (G6PI)-induced arthritis with age in two different mouse strains. METHODS: Young and very old mice from two different arthritis-susceptible wild-type mouse strains were analyzed after a single subcutaneous injection of G6PI s.c. The metabolism and the function of synoviocytes were analyzed in vitro, the production of bioactive lipid mediators by myeloid cells and synoviocytes was assessed in vitro and ex vivo by UPLC-MS-MS, and flow cytometry was used to verify age-related changes of immune cell composition and function. RESULTS: While the severity of arthritis was independent from age, the onset was delayed in old mice. Old mice showed common signs of immune aging like thymic atrophy associated with decreased CD4+ effector T cell numbers. Despite its decrease, the effector T helper (Th) cell compartment in old mice was reactive and functionally intact, and their Tregs exhibited unaltered suppressive capacities. In homeostasis, macrophages and synoviocytes from old mice produced higher amounts of pro-inflammatory cyclooxygenase (COX)-derived products. However, this functional difference did not remain upon challenge in vitro nor upon arthritis reactions ex vivo. CONCLUSION: While old mice show a higher baseline of inflammatory functions, this does not result in increased reaction towards self-antigens in arthritis-susceptible mouse strains. Together, our data from two different mouse strains show that the susceptibility for G6PI-induced arthritis is not age-dependent.
EVALuna2:528874